Reasons for hospitalization of people with dementia-A scoping review - Stiefler, Susanne; Dunker, Ellen; Schmidt, Annika; Friedrich, Anna-Carina; Donath, Carolin; Wolf-Ostermann, Karin (Zeitschrift für Gerontologie und Geriatrie, 2022)
Background Hospitalization represents a high burden for people with dementia, which can accelerate the decline of cognitive and motor skills. Behavioral changes and orientation problems may be increased in people with dementia during hospitalization. Some hospitalizations are potentially preventable by improved outpatient care. Objective To provide an up to date overview of the most common reasons for hospitalization of people with dementia or mild cognitive impairment. Material and methods A systematic literature search was conducted in the databases PubMed (R), CINAHL and PsycINFO (R) in May 2020 to conduct the scoping review. Studies in German and English published between July 2010 and May 2020 were included. Results The most common reasons for hospitalization, which were named in the 14 included studies, were infectious diseases, especially respiratory infections and urinary tract infections, cardiovascular diseases (in general or specific, e.g. heart failure) and injuries, poisoning, fractures and falls, and gastrointestinal diseases. Conclusion Most of the most common reasons for hospitalization are ambulatory care-sensitive hospital cases. Strengthening outpatient care for people with dementia may help prevent hospitalizations.
CRIS-Team WoS Importer:2022-04-29